(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The study aimed to identify the differences between the average scores of the sample on the list of aggressive behavior according to several variables (educational level of father and mother, size of family and gender) in a sample of students of the first basic education in Tartous city school’s, the sample consisted of (125) (83) males and (42) females, the tool of the study was a behavioral list based on the teacher’sEstimation prepared by the researcher.The results of the study: 1. there is significant differences between the average scores of males and females on the list of aggressive behavior and for males. 2 - There are no significant differences between the average scores of the sample on the behavioral list according to the variables of the educational level of the father 3- There are no significant differences between the average scores of the sample on the behavioral list according to the variables of the educational level of the mother, 4- There are no significant differences between the average scores of the sample on the behavioral list according to the size of the family.